The prebiotic and anti-fatigue effects of hyaluronan - Huang, Guoxin; Su, Lu; Zhang, Ni; Han, Ruixuan; Leong, Wai Kit; Li, Xiaoang; Ren, Xuecong; Hsiao, W. L. Wendy (Frontiers in Nutrition, 2022)
Hyaluronan (HA) is a mucopolysaccharide that naturally exists in all living organisms as the main component of the extracellular matrix. Over the last 30 years, HA has been used as the main ingredient in cosmetic products, eye drops, and medicinal products. It is also taken orally as a health supplement. However, the physiological effect of the ingested HA is not clear. In the current study, the interaction between HA and gut microbiota, and the potential prebiotic effects were investigated. HA was used to treat the C57BL/6 mice for 15 consecutive days, then fecal genomic DNA was extracted from fecal samples for 16S rRNA amplicon sequencing. The results showed that HA could significantly change the composition of gut microbiota (GM), e.g., increased the relative abundance of beneficial bacteria, including short-chain fatty acids (SCFAs)-producing bacteria and xylan/cellulose-degrading bacteria, whereas decreased the relative abundance of potential pathogens including sulfate-reducing bacteria (SRB), inflammation and cancer-related bacteria. The rotarod test was used to evaluate the anti-fatigue effects of HA in C57BL/6 mice. The results showed that HA could lengthen the mice's retention time on the accelerating rotarod. HA increased the concentration of glycogen and superoxide dismutase (SOD) in mice's muscle and liver, whereas decreased the serum concentration of malondialdehyde (MDA). Moreover, the metabolic products of Desulfovibrio vulgaris (MPDV), the model SRB bacteria, showed cytotoxic effects on H9c2 cardiomyocytes in a dosage-dependent manner. MPDV also caused mitochondrial damage by inducing mitochondrial fragmentation, depolarization, and powerless ATP production. Taken together, we show that HA possesses significant prebiotic and anti-fatigue effects in C57BL/6 mice.